From Grassroots to Green Deen: Women’s Roles in Climate Change Adaptation in the Coastal Area - Dewi Anggraeni; Maghfur Ahmad; Siti Mumun Muniroh; Miftahul Huda; Arumaisa Alfa Mulia; Slamet Suharto (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2025)
Climate change has emerged as a major challenge for coastal communities in Pekalongan. This study emphasizes that coastal women are not merely victims of climate change, but also key actors in fostering ecological awareness and community resilience. The research aims to explore the strategic roles of women in responding to climate change through a faith-based Green Deen and community-centered approach. This qualitative study employs a Participatory Action Research (PAR) framework, engaging coastal women as active agents in formulating and implementing climate adaptation strategies. The findings reveal that coastal women go beyond their domestic roles to become agents of ecological transformation. They actively contribute to climate adaptation through tangible actions such as environmental conservation, land use initiatives, local tradition revitalization, and spiritual reinforcement. The concept of Green Deen serves as both an ethical and practical foundation, bridging faith, action, and environmental sustainability. These findings also highlight the importance of integrating local knowledge, religious values, and participatory approaches in the development of climate adaptation policies in coastal areas.